Financial Health and Corporate Performance of Listed Manufacturing Companies in South Korea and Taiwan: A Comparative Study of the Two Asian Tigers - FOO, See Liang (Institutional Knowledge at Singapore Management University, 2016)
South Korea and Taiwan are two leading economies in Asia Pacific. This study examines the relationship between the financial health, as measured by the Altman Z-Score, and corporate performance, as measured by the Return on Equity (ROE), of listed manufacturing companies in these two markets. A linear regression was conducted between these variables to determine the magnitude and direction of their relationships. The trends of Z-Scores over a fourteen-year period are also analyzed. The analysis covers the period from 2000 to 2013(inclusive) and yielded a statistically positive correlation between ROE and the Z-Score for both markets. South Korea and Taiwan both registered moderate-to-strong mean and median Z-Scores. However, Taiwan is comparatively healthier. These findings further support the economic stature of these two markets as Asian tigers.